Efficacy Evaluation of Meropenem Against Resistant Staphylococcus hominis in Heart Failure Patients - Arif, Zainab N.; Al-Daamy, Alaa A. H.; Alhidary, Ahmed Q. (Scientific Journal of Medical Research, 2022)
Objective: This study aimed to Prepare nanohybrid from meropenem antibiotic and evaluation of its inhibitory effect against Staphylococcus hominis isolated from heart failure patients. Methods: A nanohybrid antibiotic Meropenem-ZnO was prepared using direction exchange between antibiotic meropenem and zinc oxide layers (ZnO). The new nano antibiotic was identified by Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD), Atomic Force Microscope (AFM), and scanning electron microscopy (SEM). The antimicrobial activity of the nanohybrid meropenem was studied against Staphylococcus hominis isolated from heart failure patients in the Care Center Unite (CCU) of Hospital of Imam Hussain Medical City in Karbala, that diagnosed of bacterial done by the devices Vitek. Results: The results showed that FTIR spectroscopy results for the prepared antibiotics showed that the frequencies of some chemical groups shifted towards high and low frequencies. XRD also revealed the emergence of new diffraction planes in the spectrum of the nanohybrid antibiotic compared to the carrier spectrum Zinc oxide, which indicates that the prepared antibiotics understudy is nanohybrid antibiotics, Results of atomic force microscopy (AFM) showed that the mean dimensions of the nanoparticles diameters of the Meropenem-ZnO was 145.7 nanometers. The results of scanning electron microscopy (SEM) were converting irregular shapes of zink oxid into different geometric shapes interspersed with large spaces when forming the hybrid nanocomposite (Meropenem-ZnO) resulting from the direct interaction of the zinc oxide layers with the Meropenem antibiotic. Conclusion: The efficacy of the nanohybrid Meropenem antibiotic in inhibition of isolated bacteria from heart failure patients.